Should courts always enforce what contracting parties write? - Luca Anderlini; Leonardo Felli; Andrew Postlewaite (Center for Economic Studies and ifo Institute (CESifo), 2006)
We find an economic rationale for the common sense answer to the question in our title courts should not always enforce what the contracting parties write. We describe and analyze a contractual environment that allows a role for an active court. An active court can improve on the outcome that the parties would achieve without it. The institutional role of the court is to maximize the parties' welfare under a veil of ignorance. We study a buyer-seller multiplewidget model with risk-neutral agents, asymmetric information and ex-ante investments. The court must decide when to uphold a contract and when to void it. The parties know their private information at the time of contracting, and this drives a wedge between ex-ante and interim-efficient contracts. In particular, if the court enforces all contracts, pooling obtains in equilibrium. By voiding some contracts the court is able to induce them to separate, and hence improve ex-ante welfare. In some cases, an ambiguous court that voids and upholds both with positive probability may be able to increase welfare even further.
Keywords: C79; D74; D89; K40; L14; 330; Gerichtsbarkeit; Asymmetrische Information; Public Choice; Wohlfahrtstheorie